ATSAR AL QURAN AL KARIM FI AL LUGHAH AL ARABIYYAH - Uril Bahrudin (Jurnal Alsinatuna, 2016)
The study about Qur’an and its influence on Arabic language shows the importance of language study. The aim of this research is to find out the historical study of the influence of Qur’an on Arabic language which focuses on the basics, function, and characteristics of language. The article result shows that (1) the basics of language is speaking which express or understand social, cultural, psychological and mental problems. (2) Arabic language has its own characteristics such as the uniqueness in its sound, isytiqoq, I’rab, synonym, and simplicity. (3) Qur’an makes Arabic language well-preserved, stronger, and stable. In addition, it also makes Arabic language become international language and academic language which consequently brings out Arabic education program and Arabic language development.